An assessment of the materials and methods used in disseminating information on human trafficking in two barangays of Quezon City - Tojos, Leticia S. (2010)
Given the importance of popularizing human trafficking as a human rights issue, this study looks into the initiatives of local officials and non-government organizations in Barangays Botocan and Escopa 3 in Quezon City to disseminate information among residents. The assessment covered the following areas: messages or content of the materials, methods and media for disseminating information, consumers and extent of dissemination, and effects on receivers of information.
Data gathering was done by reviewing available information dissemination materials, interviewing key informants, and conducting focus group discussion with selected residents.
Findings show that the Quezon City government has a number of instructive materials on human trafficking that have targeted its social workers and other frontline service providers, and barangay officials and residents. The materials promote the human rights perspective. However, the contents or messages have not been fully understood by barangay residents. Methods of dissemination have also not facilitated comprehension and retention of information.This was because human trafficking as a topic was only one among several inputs to the barangays without benefit of discussion.
Positive outcomes of the efforts include the improved handling of human trafficking cases by direct service workers and local officials as well as reporting of cases by residents.